Digital Image Watermarking Technique Based on ROI Using DCT and DWT Hybrid Technique - Seddeq. E. Ghrare ,Hajer. A. Emhemed , A. Adhim Mohamad Alamari (Journal of Pure & Applied Sciences, 2019)
Watermarking is the process of inserting predefined patterns into multimedia data in a way that the degradation of quality is minimized and remain at an imperceptible level. Many digital watermarking algorithms have been proposed in special and transform domains. Least Significant Bit (LSB), Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) are the common used for watermarking techniques In this paper, a hybrid watermarking technique based on DCT and DWT is proposed. An implementation of the two standalone watermarking techniques is carried out as well. A comparison between the three techniques is presented. This comparison was carried out using PSNR, MSE, and SSIM. The SSIM results were very close to 1 using DWT and the hybrid proposed technique, which means that the recovered watermarks from watermarked image were not distorted in those two cases compared with DCT. The MSE calculated values show that the smallest MSE value was obtained from the DWT, followed by hybrid technique then DCT, whereas the greatest PSNR values were obtained from DWT followed by hybrid proposed technique. The findings showed that the proposed hybrid technique was similar to DWT and more efficient compared to DCT technique.